Investigation On The Crime Of Violent Theft In The Criminal Justice System In The Resort Police Of The Big City Of Palembang - Albert Agus Topan; Abdul Latif Mahfuz (DE LEGA LATA: JURNAL ILMU HUKUM, 2023)
The current phenomenon is the crime of theft with violence or often known as robbery which is no less lively than other criminal acts. The formulation of the problems in this study are 1) How is the investigation of the crime of theft with violence in the criminal justice system at the Palembang City Police?; 2) What are the obstacles encountered in the process of investigating the crime of theft with violence in the criminal justice system at the Palembang City Police? The research method used is empirical juridical research. Sources of data used in this study consist of primary data and secondary data. Based on the results of the study, it shows that 1) Investigations into criminal acts of theft with violence in the criminal justice system at the Palembang City Police Resort have been carried out in accordance with the Criminal Procedure Code and the Law on the Indonesian National Police No. 2 of 2002, but not quite optimal. 2) Obstacles faced in Investigating the crime of theft with violence in the criminal justice system at the Palembang City Police, namely a) Obstacles to law enforcement officers. The lack of investigators makes it difficult to quickly find the identity of the suspect and the evidence used to commit theft by force or evidence of stolen objects; b) Constraints are low in public awareness. The unwillingness of the community as a witness so that the testimony of the witnesses, and c) Constraints, lack of advice and infrastructure